Identification of a putative α-galactoside β-(1 → 3)-galactosyltransferase involved in the biosynthesis of galactomannan side chain of glucuronoxylomannogalactan in Cryptococcus neoformans - Kadooka, Chihiro; Tanaka, Yutaka; Hira, Daisuke; Oka, Takuji (Frontiers in Microbiology, 2024)
Cell surface of Cryptococcus neoformans is covered by a thick capsular polysaccharide. The capsule is the most important virulence factor of C. neoformans; however, the complete mechanism of its biosynthesis is unknown. The capsule is composed of glucuronoxylomannan (GXM) and glucuronoxylomannogalactan (GXMGal). As GXM is the most abundant component of the capsule, many studies have focused on GXM biosynthesis. However, although GXMGal has an important role in virulence, studies on its biosynthesis are scarce. Herein, we have identified a GT31 family β-(1→3)-galactosyltransferase Ggt2, which is involved in the biosynthesis of the galactomannan side chain of GXMGal. Comparative analysis of GXMGal produced by a ggt2 disruption strain revealed that Ggt2 is a glycosyltransferase that catalyzes the initial reaction in the synthesis of the galactomannan side chain of GXMGal. The ggt2 disruption strain showed a temperature-sensitive phenotype at 37°C, indicating that the galactomannan side chain of GXMGal is important for high temperature stress tolerance in C. neoformans. Our findings provide insights into complex capsule biosynthesis in C. neoformans.